DEVELOPMENT OF TRADITIONAL SAGO PROCESSOR IN MALUKU: OPPORTUNITIES AND CHALLENGES FOR SUPPORTING FOOD DIVERSIFICATION - Inta P.N. Damanik; Siti Amanah; Siti Madanijah; Prabowo Tjitropranoto (UNEJ e-Proceeding, 2012)
Sago is one of the local food Maluku society that has the potential to be developedin support of diversification in Maluku in particular and Indonesia in general. Associatedwith the potential of existing sago, the role of traditional sago processing is becomingincreasingly important in processing sago into products that are more varied to support thediversification of food. This study aims to uncover the opportunities and challengesassociated with the development of traditional sago processing in Maluku in relation to thediversification of food by taking in some sites of traditional sago-processing centers inCentral Maluku regency. The results showed that there are some opportunities that areopen to developing the traditional sago processing, but these opportunities will be used ifaccompanied by efforts to address the challenges faced by the traditional sago processingin producing processed products sago.